2013
DOI: 10.1063/1.4790159
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-detonation combustion in explosives incorporating aluminum nanoparticles: Influence of the passivation layer

Abstract: Aluminum nanoparticles and explosive formulations that incorporate them have been a subject of ongoing interest due to the potential of aluminum particles to dramatically increase energy content relative to conventional organic explosives. We have used time-resolved atomic and molecular emission spectroscopy to monitor the combustion of aluminum nanoparticles within the overall chemical dynamics of post-detonation fireballs. We have studied the energy release dynamics of hexahydro-1,3,5-trinitro-1,3,5-triazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Many subsequent investigations using emission spectroscopy have utilized spectral features in the UV/visible/near-IR to interrogate the temporal dynamics [14][15][16][17][18][19][20]. This region of the spectrum corresponds to electronic transitions of both atomic and molecular species, although we note that vibrational overtones and combination bands can be observed in the near-IR.…”
Section: Molecular Emission Spectroscopy In the Uv/visible/near-irmentioning
confidence: 99%
See 3 more Smart Citations
“…Many subsequent investigations using emission spectroscopy have utilized spectral features in the UV/visible/near-IR to interrogate the temporal dynamics [14][15][16][17][18][19][20]. This region of the spectrum corresponds to electronic transitions of both atomic and molecular species, although we note that vibrational overtones and combination bands can be observed in the near-IR.…”
Section: Molecular Emission Spectroscopy In the Uv/visible/near-irmentioning
confidence: 99%
“…In this approach, the emission spectrum is analyzed qualitatively but chemical dynamics are tracked quantitatively; that is the various peaks and bands in the spectrum are identified and their intensities are plotted as a function of time in order to obtain kinetics information about chemical processes occurring in the fireball [14,15]. This approach has been used in a number of investigations to examine chemical dynamics in fireballs produced following detonation of explosive charges containing aluminum [14][15][16][18][19][20] or silver [16] by tracking the time dependence of atomic Al lines, AlO bands, and atomic Ag lines.…”
Section: Molecular Emission Spectroscopy In the Uv/visible/near-irmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 These analytes were specifically chosen because they provided a range of particle sizes, compositions, surface chemistries, and reactivities. [44][45][46][47] For example, previous studies have shown that protecting agents including organic ligands 40,[48][49][50][51][52][53][54] and polymer [55][56][57] or metal coatings 44,58,59 enhanced reactivity properties and provided chemical control over structural attributes like particle size and monodispersity. The STXM-XAS results were consistent with earlier spectromicroscopy studies, 26,55,60 and also revealed new differences in the surface and micron-scale speciation of Al nanoparticles.…”
Section: Introductionmentioning
confidence: 99%